2001
DOI: 10.1248/jhs.47.54
|View full text |Cite
|
Sign up to set email alerts
|

Removal Efficiency of Defatted Seed for Organochlorine Compounds.

Abstract: Defatted seeds effectively adsorbed organochlorine compounds such as chloroform, dichloromethane and trichloroethylene. The amounts of these compounds adsorbed was plotted against the equilibrium concentration of substances in solution on a logarithmic scale. A linear relationship was obtained, indicating that the adsorption reactions were Freundlich type. The adsorption of these compounds by defatted seed was observed over the range of pH 1-11. Chloroform was successfully removed from tap water with an averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The regression coefficient (R 2 ) values show better applicability of Freundlich model on CGAC, WGAC and BGAC. These results were in agreement for the adsorption of DCM on defatted seeds [23]. …”
Section: Adsorption Isothermssupporting
confidence: 85%
“…The regression coefficient (R 2 ) values show better applicability of Freundlich model on CGAC, WGAC and BGAC. These results were in agreement for the adsorption of DCM on defatted seeds [23]. …”
Section: Adsorption Isothermssupporting
confidence: 85%
“…Adachi et al [2,11] used rice bran and defatted seeds of soybean, rapeseed, linseed and sesame for the removal of organochlorine compounds and benzene from industrial wastewaters and obtained appreciable results. Damaris [12] employed rice husk for the adsorption and detection of phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pesticides of moderately to highly hydrophobic nature, like atrazine, have shown fairly good removal efficiencies when RS cake was used (yet, mainly due to the absorption in the oil droplets that remain trapped in the matrix after seed pressing) [61]. Higher efficiencies than powdered AC were obtained for volatile organic compounds, where some intracellular fat particles named spherosomes are responsible for their uptake [94,95].…”
Section: Mono-component Systems: Organics Adsorptionmentioning
confidence: 99%
“…Studies on sorption processes with rape biomass involving real effluents were reported by few authors [71,80,94,98,111]. Heavy metals have been successfully removed from industrial effluents: Cu from smelting wastewater in Canada using CM [78], Pb from spiked industrial wastewater in Romania (94% efficiency in biosorption column with RS meal) [71] and Cd (20% reduction) and Cu (95% removal) from acid mine water in Australia by using biochar obtained from canola shoot [80].…”
Section: Multi-component Systemsmentioning
confidence: 99%